Adapting Conceptual Frameworks for Patient Engagement in Emergency Department Research. (25th November 2016) - Wright (née Blackwell), Rebecca; Carden, Donna. L.; Hess, Erik P.; Booker‐Vaughns, Juanita; Dunn, Patrick; Kizzie‐Gillett, Constance; Vaughan, William; Weingarten, Gail; Williams, Pluscedia; Young‐Brinn, Angela; Grudzen, Corita
Abstract: For many people the emergency department (ED) is the first point of access to healthcare for acute needs and a recurring location for many with chronic healthcare needs. While the ED is well placed to identify unmet needs it can also be a net that people slip through when faced with uncoordinated and expensive healthcare challenges. Thus the ED has a responsibility to set patients on a safe and meaningful care trajectory, which can only be done in consultation and partnership with the patients themselves. The purpose of this article is to present crucial aspects of patient engagement that are essential for future research to foster an environment of colearning and respect that encourages ongoing involvement by patients, families, and staff.